2003
DOI: 10.1002/jcp.10408
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intracellular pH inhibits constitutive expression of Cyclooxygenase‐2 in human colon cancer cells

Abstract: Cyclooxygenase-2 (COX-2) over-expression is critically involved in tumor formation. Intracellular pH (pHi) has been shown to be alkaline in cancer cells, and to be an important trigger for cell proliferation. This study therefore analyzed the relationship between pHi and COX-2 expression. HRT-18 and Caco-2 cells cultured in medium with bicarbonate maintained a pHi of approximately 7.6, which is higher than that of non-neoplastic cells. Cells grown in bicarbonate-free medium with a pH at 6.8 showed a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Lotspeich (22), in his pioneering studies, was the first to show that the response to metabolic acidosis was more catholic than recognized despite lacking an understanding of underlying signaling pathways (2); in this regard, NH 4 Cl-induced metabolic acidosis and transient ERK activation may induce renal hyperplasia (22), whereas TROinduced sustained ERK activation may inhibit proliferation (20,35,36,41) and even in PPAR␥-negative cells (35,41). Such a model may also explain how extracellular acidosis (transient MAPK activation) upregulates tumorgenic cyclooxgenase-2 expression (38) while sustained intracellular acidosis [although difficult to achieve by reducing extracellular pH in normal (18) and, especially, in more alkaline tumor cells (41)] can inhibit expression of cyclooxgenase-2 in colon cancer cells (31). These studies, as well as the present findings, suggest potentially important but ill-defined relationships between acute and sustained MAPK activation and pH i in regulating growth in normal as well as malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lotspeich (22), in his pioneering studies, was the first to show that the response to metabolic acidosis was more catholic than recognized despite lacking an understanding of underlying signaling pathways (2); in this regard, NH 4 Cl-induced metabolic acidosis and transient ERK activation may induce renal hyperplasia (22), whereas TROinduced sustained ERK activation may inhibit proliferation (20,35,36,41) and even in PPAR␥-negative cells (35,41). Such a model may also explain how extracellular acidosis (transient MAPK activation) upregulates tumorgenic cyclooxgenase-2 expression (38) while sustained intracellular acidosis [although difficult to achieve by reducing extracellular pH in normal (18) and, especially, in more alkaline tumor cells (41)] can inhibit expression of cyclooxgenase-2 in colon cancer cells (31). These studies, as well as the present findings, suggest potentially important but ill-defined relationships between acute and sustained MAPK activation and pH i in regulating growth in normal as well as malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA free RNA was isolated with the SV total RNA isolation system (Promega, Madison, WI) according to the manufacturer's protocol. Reverse transcription-PCR (RT-PCR) was done as described earlier (20). The following 14-3-3j -specific primers was used: forward 5V -AGAGCGAAACCTGCTCTCAG-3V and reverse 5V -GGCATCTCCTTCTTGCTGAT-3V .…”
Section: Methodsmentioning
confidence: 99%
“…pHi was also one of the factors thought to control the rate of cell proliferation and invasion (18,19). In many tumor cell lines pHi was more alkaline than in normal cell lines (9).…”
Section: Discussionmentioning
confidence: 99%
“…Using confocal laser microscopy and BCECF labeled cells Pirkebner et al reported identical pH values in the cytosol and the nucleus (18). In contrast, a 0.3-0.5 pH unit higher pH in the nucleus than in the cytosol was found using SNARF-1 as pH indicator (25).…”
mentioning
confidence: 99%